Assessing the Potential of Renewable Energy Technologies for Sustainable Irrigation and Smallholder Farm Productivity - Olamidotun Nurudeen Michael; Omodolapo Eunice Ogunsola (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Sustainable irrigation remains a cornerstone of agricultural productivity and food security, particularly for smallholder farmers in developing regions facing water scarcity, energy poverty, and climate variability. This review examines the potential of renewable energy technologies (RETs)—including solar, wind, biomass, micro-hydropower, and hybrid systems—in transforming irrigation systems toward sustainability and resilience. It explores how the integration of RETs enhances water-use efficiency, reduces greenhouse gas emissions, and lowers operational costs, thereby improving smallholder livelihoods. The study synthesizes recent advances in renewable-powered irrigation technologies, evaluates their economic feasibility, environmental performance, and technical adaptability, and identifies policy and infrastructural enablers required for large-scale adoption. Furthermore, the review highlights innovative financing mechanisms, digital integration through IoT-based monitoring, and the role of public–private partnerships in scaling these systems. The findings suggest that a multi-stakeholder approach, supported by robust policy frameworks and localized energy-water-food nexus planning, is essential to unlock the full potential of renewable energy technologies for sustainable irrigation and rural development.